Memes nas redes sociais: um instrumento de disputa ideológica (2016-2019) - Silva , Vanile Cassimiro da (2022)
The present dissertation investigates the use of internet memes as a dispute instrument of world conceptions in Brazil via social networking websites, between the years of 2016 and 2019. The advance of new communication and information technologies has made it possible to emerge new forms of organization as well as the deepening of capitalism, which has reflected directly into the 21st century class struggle dynamics. Thus, we debate the role played by memes in the consensus production process and also from the Discourse Analysis tools, we seek to map what are the meanings built through this feature that is being disputed, both by groupings that are positioned to the right and to the left. The differences and permanences of humorous processes linked to these productions also are part of this work. The sources used go through published memes by the Anticomunismo, Barbie e Ken Cidadãos de Bem, Comunistas Expropriados and Corrupção Brasileira Memes webpages, as well as its meme creator website, the CBM Generator.